Arbuscular Mycorrhiza-Mediated Regulation of Polyamines and Aquaporins During Abiotic Stress: Deep Insights on the Recondite Players - Sharma, Karuna; Gupta, Samta; Thokchom, Sarda Devi; Jangir, Pooja; Kapoor, Rupam (Frontiers in Plant Science, 2021)
Environmental stresses of (a)biotic origin induce the production of multitudinous compounds (metabolites and proteins) as protective defense mechanisms in plants. On account of the regulation of some of these compounds, arbuscular mycorrhizal fungi (AMF) reinforce the inherent tolerance of plants toward the stress of different origins and kind. This article reviews two specific fundamental mechanisms that are categorically associated with mycorrhiza in alleviating major abiotic stresses, salt, drought, and heavy metal (HM) toxicity. It puts emphasis on aquaporins (AQPs), the conduits of water and stress signals; and polyamines (PAs), the primordial stress molecules, which are regulated by AMF to assure water, nutrient, ion, and redox homeostasis. Under stressful conditions, AMF-mediated host AQP responses register distinct patterns: an upregulation to encourage water and nutrient uptake; a downregulation to restrict water loss and HM uptake; or no alterations. The patterns thereof are apparently an integrative outcome of the duration, intensity, and type of stress, AMF species, the interaction of fungal AQPs with that of plants, and the host type. However, the cellular and molecular bases of mycorrhizal influence on host AQPs are largely unexplored. The roles of PAs in augmenting the antioxidant defense system and improving the tolerance against oxidative stress are well-evident. However, the precise mechanism by which mycorrhiza accords stress tolerance by influencing the PA metabolism per se is abstruse and broadly variable under different stresses and plant species. This review comprehensively analyzes the current state-of-art of the involvement of AMF in “PA and AQP modulation” under abiotic stress and identifies the lesser-explored landscapes, gaps in understanding, and the accompanying challenges. Finally, this review outlines the prospects of AMF in realizing sustainable agriculture and provides insights into potential thrust areas of research on AMF and abiotic stress.